The complete mitochondrial genome of a yeti crab Kiwa tyleri Thatje, 2015 (Crustacea: Decapod: Anomura: Kiwaidae) from deep-sea hydrothermal vent - Dongsheng Zhang; Yadong Zhou; Hong Cheng; Chunsheng Wang (Mitochondrial DNA. Part B. Resources, 2017)
The complete mitochondrial genome of Kiwa tyleri (Anomura, Chirostyloidea, Kiwaidae) was recovered by next generation sequencing. The mitogenome is 16,865 bp in length and contains 13 protein-coding genes (PCGs), 22 transfer RNAs (tRNAs), two ribosomal RNAs (rRNAs) and a 1525bp non-coding AT-rich region. This is the first mitogenome for the family Kiwaidae and the superfamily Chirostyloidea. The inversion of three consecutive genes (16S rRNA, tRNA-Val, 12S rRNA) was first reported for the Anomura. The phylogenetic tree indicated that Kiwaidae was close to Paguroidea and Lithodoidea rather than Galatheoidea.